2016
DOI: 10.1038/srep28175
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cumulative Incidence of Dermatomyositis in Ulcerative Colitis: a Nationwide Cohort Study

Abstract: On a molecular level, two autoimmune diseases: ulcerative colitis (UC) and dermatomyositis share common genetic determinants. On a clinical level, case reports evidenced the co-occurrence of these two diseases. We therefore hypothesize that UC is potentially associated with increased cumulative incidence of dermatomyositis. The goals of this retrospective cohort study were to evaluate whether UC is associated with increased cumulative incidence of dermatomyositis independent of sex and age. For comparison, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“… 19 In adult studies, the incidence of DM is higher in patients with ulcerative colitis (UC) compared to control groups, and the presence of UC may actually be a risk factor for DM. 20 Given that the entire clinical picture is compatible with JDM, and that there are no reports of mesalazine inducing JDM, her disease was likely not drug-induced. As a precaution, our patient discontinued mesalazine and continued MTX, high-dose prednisone, IVIG, and hydroxychloroquine to treat her colitis, skin manifestations, and myositis.…”
Section: Discussionmentioning
confidence: 98%
“… 19 In adult studies, the incidence of DM is higher in patients with ulcerative colitis (UC) compared to control groups, and the presence of UC may actually be a risk factor for DM. 20 Given that the entire clinical picture is compatible with JDM, and that there are no reports of mesalazine inducing JDM, her disease was likely not drug-induced. As a precaution, our patient discontinued mesalazine and continued MTX, high-dose prednisone, IVIG, and hydroxychloroquine to treat her colitis, skin manifestations, and myositis.…”
Section: Discussionmentioning
confidence: 98%
“…Apart from GMS, orbital myositis, which is currently considered as a subtype of idiopathic orbital inflammation, has also been reported in patients with IBD, mainly CD[ 5 ]. Few cases of dermatomyositis (DM) and polymyositis have also been described during the course of IBDs and a recent study showed that DM was more frequent in ulcerative colitis patients than CD patients and control subjects[ 7 ]. Nevertheless, the true incidence of IM occurring in this context is probably underestimated as myalgia can be confused with joint manifestations or with non-inflammatory muscle disorders ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…IBD can be associated with DM[ 6 , 7 ]. The results of Tseng et al [ 16 ] showed that the cumulative incidence of DM in patients with UC is higher than that of the control group, and UC is positively correlated with DM. We suspect that their correlation is caused by their similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%